STATE ASSET MANAGEMENT POLICY REFORM IN INDONESIA (A Case Study on Surabaya State Asset and Auction Service Office, East Java Province) - Inarto, Koko (Jurnal Ilmiah Administrasi Publik, 2013)
Abstract: State Asset Management Policy Reform In Indonesia (A Case Study on Surabaya State Asset and Auction Service Office, East Java Province). The state asset management reform in Indonesia is conducted to meet with an ideal asset management that based on the principle of âhighest and best use of assetâ and the three orders, namely law order, administrative order, and physical order. Therefore, efforts to make improvements and optimization of it are to realize the value of professional and efficient state asset management. Nevertheless, Indonesian state-owned assets are many and varied in scattered locations, so that needs time to reorganize its management. This study analyzed how is the implementation of state asset management reform policy and identified the parts of state asset framework that has to be improved as the consideration in making policies related to it in the future. This study was done by case study at Surabaya State Asset and Auction Service Office as the vertical institution of Directorate General of State Asset Management. Keyword: state asset management, policy reform, central government Â  Abkstrak: State Asset Management Policy Reform In Indonesia (A Case Study on Surabaya State Asset and Auction Service Office, East Java Province). Reformasi manajemen aset negara di Indonesia dilaksanakan untuk mencapai suatu manajemen aset yang ideal dengan didasarkan pada prinsip âpenggunaan yang tertinggi dan terbaik pada asetâ dan tiga tertib, yaitu: tertib hukum, tertib administrasi, dan tertib fisik. Untuk itu, usaha-usaha perbaikan dan optimasi dilakukan untuk mewujudkan manajemen aset negara yang profesional dan efisien. Meskipun demikian, Aset-aset yang dimiliki oleh negara sangat banyak dan letaknya tersebar di seluruh wilayah Indonesia, sehingga dibutuhkan waktu yang tidak sedikit untuk mereorganisasikannya. Studi ini menganalisis bagaimana pelaksanaan kebijakan reformasi manajemen aset negara tersebut dan mengidentifikasi bagian-bagian dari kebijakan tersebut yang harus diperbaiki sebagai dasar pertimbangan pembuatan kebijakan di masa mendatang. Penelitian ini dilakukan dengan studi kasus pada Kantor Pelayanan Kekayaan Negara dan Lelang Surabaya yang merupakan instansi vertikal Direktorat Jenderal Kekayaan Negara. Â  Kata kunci: manajemen aset Negara, reformasi kebijakan, pemerintah pusat